Prefabricated panel of lightweight concrete, based on newsprint and cardboard recycled, destined for social housing. - Prieto Jiménez, Sonia (Universidad de Cuenca, 2016)
Poverty is latent in the world, and especially in the countries in developing such as ours. The poverty level brings with it the advance or retreat of a country, as well as the impediment that its citizens may possess an own housing, food and even clothing, so all Governments tend to implement housing projects in order to supplement their deficits.It is known that one of the ways to provide housing in a more optimal way, is through the prefabrication of the elements that make up housing, which helps to reduce materials costs, time of construction and workmanship.In the case of the present investigation, we have looked for new materials to be combined with those traditional, at time that we have been seeking more environmentally friendly practices, and the possibility of creating a learning space for professionals committed to poverty of many families in our country, converting to knowledge in development tools and the professionals at the nexus between those who fail to meet their needs (people) and who has the resources and the responsibility to support them (State).Keywords: Prefabricated panel, cardboard, newsprint, recycling, social housing.